2021
DOI: 10.3389/fonc.2021.639600
|View full text |Cite
|
Sign up to set email alerts
|

Identification of VWF as a Novel Biomarker in Lung Adenocarcinoma by Comprehensive Analysis

Abstract: Lung adenocarcinoma (LUAD) is one of the most malignant tumors with high morbidity and mortality worldwide due to the lack of reliable methods for early diagnosis and effective treatment. It’s imperative to study the mechanism of its development and explore new biomarkers for early detection of LUAD. In this study, the Gene Expression Omnibus (GEO) dataset GSE43458 and The Cancer Genome Atlas (TCGA) were used to explore the differential co-expressed genes between LUAD and normal samples. Three hundred sixity-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 47 publications
1
9
0
Order By: Relevance
“…Moreover, the increased deposition of ECM proteins is one of the main reasons for this. The ECM is a fundamental and important component of all tissue organs; it also interacts with tumor cells and regulates tumor growth, proliferation, differentiation, adhesion, and metastasis (42)(43)(44). Here, we confirmed that most of the core ECM genes, such as collagens, proteoglycans, and glycoproteins, were highly expressed in the LSCC tissues than in the adjacent normal mucosal tissues (Supplementary Figure 2).…”
Section: Discussionsupporting
confidence: 75%
“…Moreover, the increased deposition of ECM proteins is one of the main reasons for this. The ECM is a fundamental and important component of all tissue organs; it also interacts with tumor cells and regulates tumor growth, proliferation, differentiation, adhesion, and metastasis (42)(43)(44). Here, we confirmed that most of the core ECM genes, such as collagens, proteoglycans, and glycoproteins, were highly expressed in the LSCC tissues than in the adjacent normal mucosal tissues (Supplementary Figure 2).…”
Section: Discussionsupporting
confidence: 75%
“…In order to understand the SA-induced migratory modulation, we evaluated the effects of SA treatment over genes related to cell migration and extracellular matrix. Since the baseline expression signature of both cell lines is different, up and down-regulated genes differ between both cell lines [45][46][47], highlighting the relevance of the genetic background of the cell. For instance, we could not detect expression of TIMP3 and IL-6 in H1299 cells, while both genes presented SA-altered expression in the A549 cell line.…”
Section: Discussionmentioning
confidence: 99%
“…Secreted phosphoprotein 1 (SPP1), a hallmark gene of the EMT process, can participate in extracellular matrix (ECM)-receptor interactions and the focal adhesion response pathway to regulate tumor metastasis and invasion. SPP1 is significantly associated with adverse survival outcomes in various cancers ( Wei et al, 2020 ; He et al, 2021 ; Wang et al, 2021 ). Notably, higher SPP1 expression levels are related to a higher N stage in LUAD patients ( Guo et al, 2020 ), although the underlying mechanism has not yet been studied fully.…”
Section: Introductionmentioning
confidence: 99%